Combining Genetic, Isotopic, and Field Data to Better Describe the Influence of Dams and Diversions on Burbot Movement in the Wind River Drainage, Wyoming. Issue 3 (May 2018) - Hooley‐Underwood, Zachary; Mandeville, Elizabeth G.; Gerrity, Paul; Deromedi, Joe; Johnson, Kevin; Walters, Annika W.
Abstract: Dams and water diversions fragment habitat, entrain fish, and alter fish movement. Many Burbot Lota lota populations are declining, with dams and water diversions thought to be a major threat. We used multiple methods to identify Burbot movement patterns and assess entrainment into an irrigation system in the Wind River, Wyoming. We assessed seasonal movement of Burbot with a mark–recapture (PIT tagging) study, natal origins of entrained fish with otolith microchemistry, and historic movement with genotyping by sequencing. We found limited evidence of entrainment in irrigation waters across all approaches. The mark–recapture study indicated that out‐migration from potential source populations could be influenced by flow regime but was generally low. Otolith and genomic results suggested the presence of a self‐sustaining population within the irrigation network. We conclude that emigration from natural tributary populations is not the current source of the majority of Burbot found in irrigation waters. Instead, reservoir and irrigation canal construction has created novel habitat in which Burbot have established a population. Using a multi‐scale approach increased our inferential abilities and mechanistic understanding of movement patterns between natural and managed systems.